(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Leprosy is a neglected tropical disease and an important public health problem, especially in developing countries. It is a chronic infectious disease that is caused by Mycobacterium leprae, which has a predilection for the skin and peripheral nerves. Although it has low sensitivity, slit-skin smear (SSS) remains the conventional auxiliary laboratory technique for the clinical diagnosis of leprosy. Polymerase chain reaction (PCR) is a molecular biology technique that holds promise as a simple and sensitive diagnostic tool. In the present study, the performance of two PCR methods, using different targets, PCR-LP and PCR-P, were compared with SSS with regard to leprosy diagnosis in a reference laboratory. M. leprae DNA was extracted from 106 lymph samples of 40 patients who had clinical suspicion of leprosy. The samples were subjected to both PCR techniques and SSS. Amplification of the human b-globin gene was used as PCR inhibitor control. The specificity of both PCR techniques was 100%, and sensitivity was 0.007 and 0.015 µg/ml for PCR-LP and PCR-P, respectively. No significant difference was found between either the PCR-LP or PCR-P results and SSS results (p >; 0.05). Although PCR is not yet a replacement for SSS in the diagnosis of leprosy, this technique may be used as an efficient auxiliary tool for early detection of the disease, especially in endemic regions. This strategy may also be useful in cases in which SSS results are negative (e.g., in paucibacillary patients) and cases in which skin biopsy cannot be performed.